Comparative Study on Essential and Trace Metals in Plant Nuts Consumed in Nigeria - Ossai, E.K. (Pakistan Journal of Nutrition, 2015)
In this study five nuts, groundnut (Arachis hypogea), coconut (Cocos nucifera), nutmeg (Myristica fragrans), walnut (Juglans nigra) and Afican nutmeg (Monodora mynstica) were investigated for the following metals: potassium, sodium, calcium, iron, zinc, lead, chromium and selenium using Perkin Elmer 3110 Atomic Absorption Spectrophotometer. Maximum amount of sodium was found in coconut (1685.86±80.6 mg/kg) and the lowest in African nutmeg (34.13±2.5 mg/kg). The highest Potassium and magnesium concentrations occurred in walnut at 3110.3±40.5 and 1164.4±55.6 mg/kg, respectively whilst the least potassium and magnesium was in African nutmeg (42.25±3.5 mg/kg) and nutmeg (4.56±0.06 mg/kg), respectively. Calcium was found highest in walnut (910.25±50.3 mg/kg) and lowest in African nutmeg (7.26±0.5 mg/kg). For iron and zinc the highest value occurred in walnut at 30.24±2.1 and 19.36±2.3 mg/kg, respectively and the lowest value for iron (6.25±0.4 mg/kg) and zinc (1.25±0.03 mg/kg) were for African nutmeg and nutmeg respectively. Apart from nutmeg that has Na/K ratio of 1.505 the other nuts had Na/K ratio of less than 1 with walnut having the lowest value. Thus it can be concluded that eating of walnuts may be beneficial for hypertensive individuals as it is rich in potassium which eliminates sodium which is highly implicated in elevation of blood pressure.